(untitled) - Trần, Thị Mai (Thành phố Hồ Chí Minh, 2007)
Sách viết về những sự kiện lịch sử của Gia Định - Sài Gòn thời kỳ 1802 - 1875
Keywords: Viet Nam,Viet Nam; History,History; 19th century,19th century; Sai Gon,Gia Đinh